Structures and solvent effects on the 1H and 13C NMR chemical shifts of the family of three pro-lithospermate molecules: DFT study - Hadidjatou, Hamadou; Holtomo, Olivier; Motapon, Ousmanou (AIP advances, 2023)
The solvent effects on the structures and nuclear magnetic resonance spectroscopy of a series of three pro-lithospermate molecules are studied. These molecules include methyl pro-lithospermate, ethyl pro-lithospermate, and n-butyl pro-lithospermate, which exhibit enantiomers and diastereoisomers. The trans-oriented enantiomers were observed by Yu et al. [Nat. Prod. Res. 31(21), 2505–2512 (2017)] and are the subject of the present study. The density functional theory was validated using the gauge-including atomic orbital/B3LYP-D3BJ/6–31++G(d,p) and continuous set of gauge transformation (CSGT)/the long-range corrected Tao, Perdew, Staroverov, and Scuseria’s τ-dependent gradient-corrected correlation-exchange functional (LC-TPSS)TPSS/cc-pVTZ methods. The chemical shifts of 1H and 13C were calculated in dimethylsulfoxide (DMSO), methanol, and water. It turns out that solvent effects are weak on the geometrical parameters (bond lengths and bond angles). The harmonic oscillator model of the aromaticity index was used to calculate the aromaticity of the subunit rings. With regard to the available experimental results, the chemical shifts of 1H and 13C are reproduced better by B3LYP-D3BJ/6–31++G(d,p) than by LC-TPSSTPSS/cc-pVTZ in the DMSO medium. The solvent effects are significant on the 13C chemical shift, mostly for protic solvents, and insignificant on 1H. The vicinal spin–spin coupling constants of protons were calculated. The coupling constant of trans-olefinic and ortho-aromatic protons fits well with the experiment.